STRATEGIC ROLE OF MOTIVATION AND LEADERSHIP IN IMPROVING TEACHER PERFORMANCE - Muhdar (MBA - Journal of Management and Business Aplication, 2020)
This study is aimed at analyzing the role of motivation and leadership strategies in improvingthe performance of case study teachers in teachers at SMK Negeri Kalibaru.The data uses primary data and obtained by interview and questionnaire distribution methodwith the population in this study were all Gorvernmentalteachers of SMK Negeri KalibaruBanyuwangi with 38 people as respondents in this study. The analysis includes the instrumenttest that is the validity and reliability test, econometric evaluation or classic assumption testthat is normality test, multicollinearity test and heteroscedasticity test, model suitability testand multiple regression analysis results are obtained: Motivation has a strategic and positiverole on performance. Leadership has a strategic and positive role and is significant toperformance. So from this conclusion, Motivation and Leadership have a strategic role inincreasing teacher performance.From the results of the study, it is expected that schools andprincipals will pay more attention and improve services to teachers in motivating and leadingteachers and providing positive behavior so that teachers can work well, responsible,comfortable and improve school goals in accordance with the vision and mission of theschool.